An overview of cyber threats generated by AI - Aftab Arif; Muhammad Ismaeel Khan; Ali Raza A Khan (Information Technology and Science (ITScience), 2024)
Artificial intelligence's (AI) quick development has drastically changed cyber security by bringing in both sophisticated cyber threats and cutting-edge defenses. This research paper offers a thorough analysis of AI-generated cyber threats, including their mechanics, noteworthy case examples, and countermeasures. The report demonstrates how attackers carry out high-impact assaults, such as automated phishing, ransom ware, and misinformation campaigns, by utilizing AI tools like machine learning, natural language processing, and deep fake technologies. Important case studies highlight the necessity for enterprises to implement proactive and comprehensive security measures by illuminating the practical effects of these risks. Trends suggest that as AI-generated threats develop, they will become more sophisticated and automated due to the rise of autonomous systems that can carry out assaults without the need for human interaction. Organizations are urged to make investments in cutting-edge AI-powered security solutions, promote a cyber-security-aware culture among staff members, and create strong incident response strategies in order to address these changing issues. Enhancing collective defenses against AI-generated cyber threats requires stakeholder collaboration and information sharing, as well as frequent security assessments and adherence to ethical AI principles. This research indicates that a proactive and adaptive strategy to cyber security will be critical in guaranteeing resilience against the increasingly complex threat landscape posed by AI as enterprises traverse the intricacies of the digital era. In an interconnected world, stakeholders can cooperate to protect their assets and uphold public trust by cultivating a culture of continual development and cooperation.